2017
DOI: 10.7554/elife.25051
|View full text |Cite
|
Sign up to set email alerts
|

Lotka-Volterra pairwise modeling fails to capture diverse pairwise microbial interactions

Abstract: Pairwise models are commonly used to describe many-species communities. In these models, an individual receives additive fitness effects from pairwise interactions with each species in the community ('additivity assumption'). All pairwise interactions are typically represented by a single equation where parameters reflect signs and strengths of fitness effects ('universality assumption'). Here, we show that a single equation fails to qualitatively capture diverse pairwise microbial interactions. We build mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
262
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(281 citation statements)
references
References 75 publications
4
262
0
Order By: Relevance
“…It is possible that higher‐order interactions significantly influence community dynamics in lower dimensional multi‐species assemblages, such as three‐member consortia. Previous work showed that pairwise phenomenological models of low‐dimensional assemblages (2–3 species) trained on an interval of time of Monod‐based community models failed in some cases to predict future dynamic behaviors (Momeni et al , ). The mechanistic models considered in this study involved a limited number of metabolites, whereas numerous metabolites likely mediate microbial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that higher‐order interactions significantly influence community dynamics in lower dimensional multi‐species assemblages, such as three‐member consortia. Previous work showed that pairwise phenomenological models of low‐dimensional assemblages (2–3 species) trained on an interval of time of Monod‐based community models failed in some cases to predict future dynamic behaviors (Momeni et al , ). The mechanistic models considered in this study involved a limited number of metabolites, whereas numerous metabolites likely mediate microbial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as donor and acceptor bacteria were not in physical contact in our assay, additional contactmediated interactions (54) may affect in vivo interactions. Moreover, higher-order interactions between more than two bacteria could potentially affect community stability (20), and the complexity of such interactions may limit the predictability of simple pairwise models (55). However, a recent study found that pairwise interactions largely predict the population dynamics of larger communities (56).…”
Section: Discussionmentioning
confidence: 99%
“…The null expectation from a simple model of interactionthe generalized Lotka-Volterra modelis that an obligate species will always benefit from an increase in growth rate of its nutrient provider (Vandermeer and Boucher, 1978;Boucher et al, 1982). More recent phenomenological theory that combines the positive effects of crossfeeding with the negative effects of competition suggest that cross-feeding systems can be destabilized by the addition of cross-fed nutrients (Estrela et al, 2012;Müller et al, 2014;Hoek et al, 2016;Momeni et al, 2017). This discrepancy is because in the recent models, the net impact that one species has on the other can switch from positive to negative as the system approaches a shared carrying capacity.…”
Section: Introductionmentioning
confidence: 99%